Características físicas - mecánicas e hidráulicas del pavimento articulado en la cabecera cantonal de Guano Provincia de Chimborazo - Tierra Taraguay, Jhon Byron (2024)
The deterioration of articulated pavements is related to the action of water from rainfall, which is aggravated due to the lack of specification of a runoff coefficient in the current regulations for this type of pavement, for the design of drainage systems. These conditions represent a risk for road safety. Therefore, it is necessary to generate information on the hydraulic characteristics of articulated pavements in the cantonal head of Guano, province of Chimborazo. This research presents both laboratory and in situ data on these properties and their correlation, using electrical equipment for their measurement. The results indicate that the physical properties of the material partially comply with Ecuadorian standards for type 3 granular base courses. However, deficiencies are evident in the IN SITU properties, which are attributed to inadequate construction processes and exposure to adverse weather conditions. In particular, compaction and CBR values below those established in the standards were observed. The analysis of the hydraulic properties revealed that the runoff values for the articulated pavement coincide with the regulatory limits for flexible pavements in good condition. When correlating the physical-mechanical properties IN SITU with the hydraulic properties, an increase in the percentage of infiltration was detected in the samples with lower CBR and degree of compaction. Finally, this characterization can be valuable for the design of more adequate drainage systems, adapted to the material of the area studied, and for the implementation of new deterioration indicators in articulated pavements.